(untitled) (Biological Sciences - PJSIR, 1996)
The regression equations were determined by the least square method: Y = a + b X or log Y = log a + b log X (a, intercept; b, slope). The significance of variation in the esti- mate of slope ’b’ from the estimated value B (=3) for an ideal fish was tested by t-test at 0.05 confidence limit (CL) [10].